Quality of life perception of type 1 diabetic patients treated with insulin analogs and receiving medication review with follow-up in a public health care service from Ponta Grossa-PR, Brazil - Aline Ansbach Garabeli; Josélia Borba Daher; Astrid Wiens; Luana Lenzi; Roberto Pontarolo
ABSTRACT Glycemic control in patients with diabetes mellitus type 1 (DM1) reduces the risk of complications but requires a rigorous health care routine. Thus, diabetes education is central to increasing treatment compliance and self-care practices. This study aimed to evaluate the quality of life (QoL) and glycemic control of DM1 patients being treated with insulin analogs and receiving medication review with follow-up. This was a transversal study that included 110 patients registered at the 3rd Health Regional of Ponta Grossa-PR, aged ≥ 18 years, and receiving pharmaceutical care for at least 1 year. The Diabetes Quality of Life Measure (DQOL)-Brazil was used to evaluate QoL. The data were statistically analyzed using SPSS version 17.0 with 95% confidence levels. Of the 110 patients, 58.2% were women. The average age was 33.7 years (±10.5), and the average glycated hemoglobin (HbA1c) value was 8% (±1.4). The mean total DQOL-Brazil score was 2.11 (95% confidence interval, 2.02 - 2.21). All DQOL-Brazil scores were lower in patients with HbA1c ≤ 8%, indicating a better QoL. Good glycemic control, thus, appears to have a positive influence on the QoL, and pharmaceutical interventions are able to contribute to the achievement of therapeutic targets.